A mixture model of household retirement choice - Zhiyang Jia (University of Oslo, Department of Economics, 2003)
This paper analyzes the labor market participation behavior of the elderly couples when a new option (early retirement) becomes available to the husband. Unlike other studies of household labor supply model, which assume that all the households follow the same decision making structure, we assume there are two types of household, the cooperative type and the non-cooperative type. When facing the choice problem, those belong to the non-cooperative type behave according to a Stackelberg game with male as the leader, while those of the cooperative type follow a simple unitary model. Under this assumption, we formulate a mixture model using the latent class analysis framework. This model explicitly takes account of the unobserved heterogeneity in decision making structures. The empirical estimation of the model is based on register data from Statistics Norway. We find that more than half of the households belong to the non-cooperative type. And these households on average have lower education level than those of the cooperative type. Our conjecture is that this may suggest that it is easier for higher education couples to communicate and compromise to reach a efficient solution.
Keywords: D10; H55; J26; 330; household labor supply; retirement; latent class analysis; heterogeneity; econometric models; Ältere Arbeitskräfte; Flexible Altersgrenze; Haushaltsökonomik; Norwegen